1072 Glycaemic control in children and adolescents with type 1 diabetes around the COVID-19 pandemic. (17th August 2022) - Shinwari, Hanan; Mackenzie, Carrie; Soni, Astha; Wright, Neil; Lawrence, Neil
Abstract : Aims: The COVID-19 pandemic impacted the daily routine of children by the introduction of remote learning and telemedicine. The impact of these changes is unclear in the management of type 1 diabetes in children. The aim of this study was to evaluate the impact of several lockdowns on glycaemic control in children and adolescents with type 1 diabetes in a large paediatric hospital in the UK. Methods: This retrospective observational cohort study reviewed real world data from patients with type 1 diabetes who used glucose monitoring devices including continuous glucose monitors, flash glucose monitors or self-monitoring of blood glucose. Data was collected from four timeframes matching the dates of lockdown restrictions in the UK, T1 - 5/11/2019 to 23/3/2020, T2 - 24/3/2020 to 8/8/2020, T3 - 5/11/2020 to 23/3/2021 and T4 - 24/3/2021 to 8/8/2021. Time in Range (TIR), Mean blood sugar and standard deviation (SD) of blood sugar readings were compared across all four timeframes using paired T-tests. Results: A total of 243 children (128 male and 115 female) were included in the study with a mean age of 14.2 ± 3.71 (standard deviation) years old. The median duration of T1D was 6.15 years (IQR 4.25-8.68). There was an increase in percentage TIR between T2 vs T4 (56.8% vs 57.8%, p = 0.037) and improved glucose variability, as shown by SD between T1 vs T2 (4.57 mmol/L vs 4.44 mmol/L, p = 0.0014), T2 vs T4 (4.44 mmol/L vs 4.41 mmol/L, p = 0.0028) and T3 vs T4 (4.42 mmol/L vs 4.41 mmol/L, p = 0.027). Conclusion: Glycaemic control did not decline in children and adolescents with T1D as a result of the COVID-19 pandemic, rather%TIR and SD of blood glucose showed improvement across a series of the three UK lockdowns. Enthusiasm to revert back from telemedicine following the pandemic should be tempered by our findings that remote management has not been detrimental to glycaemic control.